PENTINGNYA PENDAMPINGAN UMKM MELALUI MODUL ILO SCORE DI TOKO SEMBAKO KEMAYO BENGKAYANG KALIMANTAN BARAT - Adot, Natalia; Sustryanti, Utami Citriana; Kristianto, Aloysius Hari; Salfarini, Eligia Monixa (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
The purpose of this service is; 1) Providing insight and understanding to Kemayo Shop Owners regarding management through the ILO Score Module, 2) Implementing and planning the 3K module, and 3) Creating Promotions on Google Maps by uploading photos of Kemayo shop locations. The methods used in the ILO SCORE module are 5S, K3 and Promotion. The results of this activity have succeeded in implementing the 5S Module, K3 Module and Promotional Module for the Kemayo Bengkayang Grocery Store. The Kemayo grocery store is one of the MSMEs in Bengkayang. The Kemayo Shop was founded in 1995. There are several problems that exist in the MSME Kemayo Shop, including the environment in the Kemayo Shop area which is still not clean and there is no social media. This is due to limited understanding in managing MSMEs which makes it difficult for shop owners to manage the shop. Therefore, it is necessary to empower MSMEs through assistance in order to improve the welfare of MSMEs in Bengkayang Regency based on the ILO Score Module.